Molecular Markers for the Prediction of Minor Response to Neoadjuvant Chemoradiation in Esophageal Cancer: Results of the Prospective Cologne Esophageal Response Prediction (CERP) Study. Issue 5 (November 2016) - Bollschweiler, Elfriede; Hölscher, Arnulf H.; Herbold, Till; Metzger, Ralf; Alakus, Hakan; Schmidt, Henner; Drebber, Uta; Warnecke-Eberz, Ute
Abstract : Objective: The aim of this study was to evaluate the predictive value of a single or combination of biomarker(s) for histopathologic non-response to neoadjuvant chemoradiation in esophageal cancer. Summary of Background Data: Patients without response to neoadjuvant chemoradiation for esophageal cancer have no prognostic benefits, but experience time delays and risk side effects. Methods: Inclusion criteria for this prospective diagnostic study were patients with cT3, Nx, M0, esophageal squamous cell or adenocarcinoma and planned neoadjuvant chemoradiation (5- fluorouracil, cisplatin, 40Gy) followed by 2-field transthoracic esophagectomy. From pretherapeutic endoscopic tumor biopsies, ERCC1 rs11615 single-nucleotide polymorphism (ERCC1-SNP) and a combination of gene expression marker mRNA (ERCC1, DPYD, ERBB2) were analyzed. ERCC1-SNP was subdifferentiated into homozygous C-allele (CC) and T-allele (TT), and heterozygous C/T carriers. The primary endpoint was the prediction of histopathological minor response (≥10% vital tumor cells in the primary tumor) relative to marker levels. Results: From 2009 until 2013, 320 patients were screened, and 85 patients (SCC n = 29, AC n = 56) were included in the study. Forty-one patients (48%) had major response with 3-year survival rate (3-YSR) of 57% compared with 44 patients with minor response and 3-YSR of 25% ( P = 0.001). Patients with ERCC1-SNP CC (n = 8) and TT (n = 37) had similar rates of minor response of 70% and 75%, and a positive predictive value (PPV) of 71% [95% confidence interval (CI 56%–84%)]. PPV increased to 89% (95% CI 73%–96%) when ERCC1-SNP was combined with mRNA markers. Conclusion: ERCC1-SNP in combination with mRNA ERCC1, DPYD, and ERBB2 from pretherapeutic endoscopic biopsies can predict minor response to chemoradiation, as a basis for individualized therapy of advanced esophageal cancer.